2022
DOI: 10.7759/cureus.22746
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Stump Syndrome With Stent-Assisted Coil Embolization

Abstract: Carotid stump syndrome (CSS) is a rare cause of recurrent ipsilateral cerebrovascular events that typically manifests as transient ischemic attacks or amaurosis fugax. The cause of these recurrent symptoms is thought to be microembolization from an occluded internal carotid artery that reaches intracranial circulation through anastomoses. We undertook a systematic literature review according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines using the PubMed, Web of Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…This type of stroke is mainly characterized by non-identifiable causes, accounting for up to 25 % of patients with stroke [9] . CSS is an uncommon disorder that was first described in 1978 [1] , [7] . A study demonstrated that an obstructed ICA increases the risk of an ipsilateral cerebrovascular accident by 3 to 5 % per year [5] , [10] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This type of stroke is mainly characterized by non-identifiable causes, accounting for up to 25 % of patients with stroke [9] . CSS is an uncommon disorder that was first described in 1978 [1] , [7] . A study demonstrated that an obstructed ICA increases the risk of an ipsilateral cerebrovascular accident by 3 to 5 % per year [5] , [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Pathophysiologically, CSS is thought to be caused by ipsilateral microembolization to the external carotid artery (ECA) and ophthalmic artery. Through retrograde collaterals, microemboli migrate to the intracranial pathways through the ECA and ophthalmic arteries [2] , [7] , [11] . The thromboemboli in the completely obstructed ICA can be the cause of cerebral embolization [2] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations